Effect of MgO Grade in MgO–C Refractories on the Non‐metallic Inclusion Population in Al‐Treated Steel. Issue 6 (11th December 2021) - Kerber, Florian; Zienert, Tilo; Hubálková, Jana; Stein, Volker; Schemmel, Thomas; Jansen, Helge; Aneziris, Christos G.
Abstract : Steelmaking processes require high‐performance lining materials with high refractoriness and thermal shock resistance, such as MgO–C bricks. Therefore, the interactions between three industrially fabricated MgO–C bricks differing in the used MgO grade and liquid steel are investigated by immersion tests in an Al‐deoxidized 42CrMo4 steel at 1600 °C, herein. The trials are carried out in a steel casting simulator. Macro‐ and microstructure of immersed specimens are characterized using light microscopy, scanning electron microscopy, and X‐ray diffraction, while the inclusion population in the solidified steel is analyzed using an automated feature analysis to determine the frequency, geometric characteristics, and elemental composition of the inclusions. Newly formed structures consisting mainly of MgO are observed on the immersed specimens differing in their superficial appearance and the frequency of phases assigned to the system Al2 O3 –CaO–MgO–SiO2 in dependence on the MgO grade. Based on the inclusion species occurring in the solidified steel, a specific rulefile is developed to classify the non‐metallic inclusions by their elemental composition. Significant differences in the frequency of detected inclusions and their distribution according to the developed rulefile depending on the MgO grade are identified by keeping the processing in the steel casting simulator constant. Abstract : Herein, the evolution of the non‐metallic inclusion population in Al‐deoxidized 42CrMo4 steel after the immersion of MgO–C specimens differing in their MgO grade is focused. In dependence of the MgO grade, significant differences in the total number of inclusions as well as their distribution according to the developed rulefile are observed.